TNFα-induced cardioprotection is independent of the activation of the prosurvival kinase Erk - Somers, Sarin; Engerer, Aurelien; Lecour, Sandrine (SA Heart Journal, 2017)
Introduction: Tumour Necrosis Factor alpha (TNFα) contributes to cardiac dysfunction following ischaemia-reperfusion. Nonetheless, brief exposure to exogenous low doses of TNFα can mimic ischaemic preconditioning and thus be cardio-protective. The extracellular signal-regulated kinase (Erk) has been implicated in the protection against ischaemia-reperfusion and is known to be activated by TNFα. However, whether Erk activation contributes to TNFα-induced cardio-protection remains unknown. Methods: PD 98059 (10μM), an Erk inhibitor, was used to evaluate the role of this prosurvival kinase with respect to infarct size (expressed as a percentage of the area at risk) in isolated rat hearts subjected to ischaemic preconditioning (IPC) or TNFα preconditioning (TNFαP). Western blot analyses were used to determine the degree of Erk phosphorylation after the application of the preconditioning stimulus. Results: Pre-treatment of the hearts with 0.5ng/ml of TNFα (for 7min) or 2 cycles of 5min ischaemia-reperfusion prior to 30min regional index ischaemia and 2h of reperfusion reduced the infarct size by 76% and 88%, respectively, versus control. Western blot analysis of isolated rat hearts revealed that IPC but not TNFαP activated phosphorylation of Erk (+54% for IPC vs. control). Coadministration of PD 98059 during the preconditioning stimulus did not influence the infarct size. Conclusion: These findings confirm that activation of TNFα may be considered as a novel therapeutic approach against ischaemic heart disease and that its effect is independent of the activation of the classic prosurvival factor Erk.